Involvement of interleukin-17A-induced hypercontractility of intestinal smooth muscle cells in persistent gut motor dysfunction. - Hirotada Akiho; Yohei Tokita; Kazuhiko Nakamura; Kazuko Satoh; Mitsue Nishiyama; Naoko Tsuchiya; Kazuaki Tsuchiya; Katsuya Ohbuchi; Yoichiro Iwakura; Eikichi Ihara; Ryoichi Takayanagi; Masahiro Yamamoto (PLoS ONE)
Background and aim The etiology of post-inflammatory gastrointestinal (GI) motility dysfunction, after resolution of acute symptoms of inflammatory bowel diseases (IBD) and intestinal infection, is largely unknown, however, a possible involvement of T cells is suggested. Methods Using the mouse model of T cell activation-induced enteritis, we investigated whether enhancement of smooth muscle cell (SMC) contraction by interleukin (IL)-17A is involved in postinflammatory GI hypermotility. Results Activation of CD3 induces temporal enteritis with GI hypomotility in the midst of, and hypermotility after resolution of, intestinal inflammation. Prolonged upregulation of IL-17A was prominent and IL-17A injection directly enhanced GI transit and contractility of intestinal strips. Postinflammatory hypermotility was not observed in IL-17A-deficient mice. Incubation of a muscle strip and SMCs with IL-17A in vitro resulted in enhanced contractility with increased phosphorylation of Ser19 in myosin light chain 2 (p-MLC), a surrogate marker as well as a critical mechanistic factor of SMC contractility. Using primary cultured murine and human intestinal SMCs, IκBζ- and p38 mitogen-activated protein kinase (p38MAPK)-mediated downregulation of the regulator of G protein signaling 4 (RGS4), which suppresses muscarinic signaling of contraction by promoting inactivation/desensitization of Gαq/11 protein, has been suggested to be involved in IL-17A-induced hypercontractility. The opposite effect of L-1β was mediated by IκBζ and c-jun N-terminal kinase (JNK) activation. Conclusions We propose and discuss the possible involvement of IL-17A and its downstream signaling cascade in SMCs in diarrheal hypermotility in various GI disorders.